ANALISIS FRAMING PEMBERITAAN VAKSIN COVID-19 OXFORD-ASTRAZENECA DI INDONESIA(Studi Pada Pemberitaan Media Kompas.com & Tempo.co Tanggal 14 - 30 Juni 2021 Dalam Pemberitaan Vaksin Oxford-AstraZeneca) - Dian Rahmawati Subakti, (2022)
Online news media is an option for actual and factual updated information sources, although not all online news sites are official and trusted news sites. There are several online news sites in Indonesia, such as Kompas.com and Tempo.co. Kompas.com is one of the most trusted online news sites in Indonesia. Kompas.com is under the control of Kompas, a journalistic mass media agency that has long been established in Indonesia, and is also a pioneer of journalism in Indonesia. In reporting on COVID-19, especially information on vaccine developments, both media such as Kompas.com and Tempo.co each frame the information obtained and then publish it in order to shape the public perception expected from these media, especially in shaping the perception of readers. Against the COVID-19 vaccine. This research method uses a qualitative approach with data collection techniques documented and analyzed using the framing model developed by Pan & Kosicki. The results showed that syntactically the framing of kompas.co news from headlines, leads, quotes, and closings, contained a lot of the AstraZeneca vaccine plan and its research updates that contained pros and cons for consumption. And closing, contains a lot of research on the AstraZeneca vaccine which is actually suitable for consumption and should be carried out by the community.